The Daya Hambat Aktinomisetes terhadap Isolat Escherichia coli Tahan Antibiotik Asal Daging Ayam yang Dilalulintaskan Melalui PelabuhanTanjung Perak Surabaya - Sari, Rakhmi Ros; Sudarwanto, Mirnawati; Lukman, Denny Widaya (Jurnal Veteriner; Vol 20 No 2 (2019)DO - 10.19087/jveteriner.2019.20.2.163, 2019)
The emergence of antibiotic-resistant bacteria is a common problem nowadays. This problem has led to more difficult treatment of infectious diseases and the higher cost of treatment for the diseases. Therefore, it is necessary to develop a new type of antimicrobial that has ability to control the pathogenic bacteria without causative resistence. The aim of this research was to measure the actinomycetes ability which produced antimicrobial againts antibiotic-resistant E. coli taken from poultry meat in Tanjung Perak Port Surabaya. The actinomycetes isolates used in this study were Streptomyces genus, Streptomyces 3 (Sp 3), Streptomyces 44 (Sp 44), Streptomyces 46 (Sp 46), Streptomyces 47 (Sp 47) and Streptomyces 413 (413). Two isolates of actinomycetes, Sp 47 and Sp 413, were found to have an inhibitory effect on the growing of antibiotic-resistant E. coli. Based on the average affect of inhibition ability, actinomycetes InaCC was the strongest while InaCC 47 was weak.